Disparities, Trends, and Predictions to 2040 in Gastrointestinal Cancer Incidence, Mortality in the United States - Huang, Ying; Huang, Hongbo; Wei, Tingting; Zhang, Aijie; Zhang, Heng; Zhang, Ze; Xu, Yijing; Wang, Ruiyao; Wan, Ningyi; Li, Xiaohan; Li, Jiaying; Li, Yunhai; et al. (The American journal of gastroenterology, 2025)
Growing gastrointestinal cancers in the United States necessitate further research due to substantial health care and economic impacts. The aim of this study was to analyze trends and future projections for 5 major gastrointestinal cancers (colorectal, pancreatic, liver, stomach, and esophageal). Data were sourced from the Surveillance, Epidemiology, and End Results database; National Center for Health Statistics; and Global Burden of Diseases databases. An age-period-cohort model using the Bayesian Information Criterion method was applied to project incidence and mortality rates to 2040. Men consistently exhibited higher incidence and mortality rates across all gastrointestinal cancers, with significant variation across the 51 US states. From 2000 to 2020, colorectal cancer incidence and mortality rates declined across all racial groups, except for the incidence rates of American Indian and Alaska Native (AIAN) men, Hispanic men, and Hispanic women, which remained stable. Pancreatic cancer incidence increased across all groups except for AIAN men, while mortality rates rose only for White men and Hispanic women. Liver cancer incidence rose among AIAN men and White, AIAN, and Hispanic women, while mortality rates declined for most groups. Stomach cancer incidence and mortality either declined or stabilized, and esophageal cancer rates showed a general decline. By 2040, increases in incidence and mortality are projected for most gastrointestinal cancers, particularly in men. Despite varied trends over the past 2 decades, an overall increase in gastrointestinal cancer incidence and mortality rates is anticipated in the next 20 years in the United States, underscoring the need for effective prevention and intervention strategies.